Selective effects of collagen-derived peptides Pro-Hyp and Hyp-Gly on the proliferation and differentiation of SSEA3-positive human dental pulp stem cells - Risako Suzuki; Kentaro Ide; Shusuke Tokuchi; Toshihiro Kawano; Edward Hosea Ntege; Makoto Murahashi; Mikana Isa; Hiroshi Sunami; Yusuke Shimizu; Hiroyuki Nakamura (Regenerative Therapy)
Introduction: Collagen-derived peptides demonstrate diverse biological activities, but their effects on human dental pulp stem cells (hDPSCs) remain unclear. This study investigated the influence of prolyl-hydroxyproline (Pro-Hyp) and hydroxyproline-glycine (Hyp-Gly) on stage-specific embryonic antigen 3 (SSEA3)-positive hDPSCs. Methods: SSEA3-positive and SSEA3-negative hDPSCs were isolated and cultured with Pro-Hyp or Hyp-Gly (200 μg/ml) under stem cell medium or differentiation-inducing conditions. Cell proliferation was assessed using the MTT assay. The expression of the chondrogenic and osteogenic markers was analyzed by real-time PCR. Matrix production was evaluated using Alcian blue and Alizarin red S staining. Results: Pro-Hyp and Hyp-Gly enhanced the proliferation of SSEA3-positive hDPSCs compared with SSEA3-negative cells. Pro-Hyp promoted chondrogenic differentiation through early upregulation of Col II followed by sustained SOX9 expression, with enhanced matrix production after 2 weeks in chondrogenic medium. Hyp-Gly specifically enhanced the osteogenic differentiation of SSEA3-positive cells through the temporal regulation of gene expression, progressing from early transcription factors (RUNX2 and RANKL) to matrix proteins (ALPL, Col I, BSP, and OCN), resulting in increased mineralization under osteogenic conditions. Conclusions: This study demonstrated that Pro-Hyp and Hyp-Gly selectively influenced SSEA3-positive hDPSC fate through the distinct temporal regulation of differentiation pathways. These findings provide new insights into the development of targeted regenerative strategies using collagen-derived peptides in dental tissue engineering.